Chylous ascites secondary to Hodgkin’s lymphoma in a HIV/aids patient: case report and literature review - Silva Júnior, Mário Luciano de Mélo; Leonídio, Hildenice Ferreira Bernardes; Lira, Mariana Montenegro de Melo; Arraes, Luciana Cardoso Martins; Padilha, Carlos Eduardo Guimarães; Araújo, Paulo Sérgio Ramos de (Medicina (Ribeirao Preto), 2017)
Study design: case report. Case report: Man, 42 years old, diagnosed with aids two years ago, had developed enlarging in abdominal volume six months from admission. Computed tomography imaging showed free liquid in peritoneal cavity and increased retroperitoneal and mesenteric lymph nodes, besides splenomegaly. Ascitic fluid had milky appearance and high triglycerides levels. Hodgkin's lymphoma (mixed cellularity) was confirmed by histopathological analysis of a video-laparoscopic lymph node biopsy, Ann Arbor IIIS staging. Chemotherapy and continuation of highly active antiretroviral therapy resulted in weight gain and reduction of abdominal volume. Chylous ascites is a rare condition, which has a vast differential diagnosis. Discussion: In our review, the majority (15/18, 83%) of chylous ascites in HIV/aids-patients are due to infectious causes (mainly Mycobacterium avium complex and tuberculosis infection), in highly immunocompromised patients (mean TCD4=87cell/mL). To the best of our knowledge, this is the first case of chylous ascites secondary to Hodgkin’s lymphoma in a patient with aids.